2D-QSAR Analysis of Oxadiazole Substituted α-Isopropoxy phenylpropionic Acids as PPAR-α & PPAR-λ Agonists. Issue 2 (2004) - L. K., Soni; A. K., Gupta; S. G., Kaskhedikar
Abstract : A quantitative structure activity relationship study on a series of oxadiazole substituted α-isopropoxy phenylpropionic acids with activity on PPAR-α and PPAR-λ was made using combination of various physiochemical descriptors. Several statistical regression expressions were obtained using stepwise multiple linear regression analysis. The best quantitative structure activity relationship model was further validated by leave one out cross validation method. Steric parameter (molar refractivity) was found to have significant correlationship with PPAR-λ agonist activity and hydrophobic (Hansch substituent constant), electronic parameter (field effect) were found to have significant correlationship with PPAR-α agonist activity. The increment in the number of carbon atom (indicative variable) between the oxadiazole tail and central phenoxy moiety increases the PPAR-λ agonist activity whereas decreases the PPAR-α agonist activity